FAKTOR-FAKTOR PENENTU RASIO PEMBAYARAN DIVIDEN PADA PERUSAHAAN NON-KEUANGAN - WISNU HERMANTO; INDRA ARIFIN DJASHAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to determine the effects of profitability, operating cash flow per share, tax, market to book value, current ratio, debt to equity ratio, and firm size towards dividend payout ratio. This study is an expansion of previous research previously written by Rehman and Takumi (2012). Data were takenfrom all companies listed at Indonesia Stock Exchange during three years (2012-2014) except for financial companies. Samples were selected based on purposive sampling method. Only 98 companies met the criteria and used as the sample. The statistical method in this study is multiple regression. The research showed thatoperating cash flow per share, tax, market to book value, debt to equity ratio, and firm size had effect to dividend payout ratio. Whereas the variable profitability and current ratio had no effect to dividend payout ratio.